2021
DOI: 10.1038/s41419-021-03493-2
|View full text |Cite|
|
Sign up to set email alerts
|

Hypothermic oxygenated perfusion inhibits HECTD3-mediated TRAF3 polyubiquitination to alleviate DCD liver ischemia-reperfusion injury

Abstract: Ischemia-reperfusion injury (IRI) is an inevitable and serious clinical problem in donations after heart death (DCD) liver transplantation. Excessive sterile inflammation plays a fateful role in liver IRI. Hypothermic oxygenated perfusion (HOPE), as an emerging organ preservation technology, has a better preservation effect than cold storage (CS) for reducing liver IRI, in which regulating inflammation is one of the main mechanisms. HECTD3, a new E3 ubiquitin ligase, and TRAF3 have an essential role in inflamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 44 publications
0
18
0
Order By: Relevance
“…Hypothermic oxygenated perfusion (HOP) prevents ischemia-reperfusion-mediated liver damage. The underlying mechanism revealed that both the DOC and HECT domains of HECTD3 induce polyubiquitination of TRAF3 at Lys138, and ubiquitinated TRAF3 promotes oxidative stress and inflammation (Zhou et al, 2021). Here, we showed that HECTD2 upregulation enhances RCC progression both in vitro and in vivo, and HIF-1α had a positives relationship with HECTD2 and increased its expression.…”
Section: Discussionmentioning
confidence: 67%
“…Hypothermic oxygenated perfusion (HOP) prevents ischemia-reperfusion-mediated liver damage. The underlying mechanism revealed that both the DOC and HECT domains of HECTD3 induce polyubiquitination of TRAF3 at Lys138, and ubiquitinated TRAF3 promotes oxidative stress and inflammation (Zhou et al, 2021). Here, we showed that HECTD2 upregulation enhances RCC progression both in vitro and in vivo, and HIF-1α had a positives relationship with HECTD2 and increased its expression.…”
Section: Discussionmentioning
confidence: 67%
“…Recombinant RANKL ameliorates HIRI [55]. TRAF3 plays an essential role in HIRI [56,57]. Hepatocytespecific knockout of TRAF3 ameliorates cell death and immune responses both in vitro and in vivo hepatic I/R models, whereas myeloid cell-specific deletion of TRAF3 does not affect HIRI [58].…”
Section: Hepatic Ischemia/reperfusion Injurymentioning
confidence: 99%
“…Hepatic ischemia/reperfusion disturbs liver function, leading to irreversible damage and even multiple organ failure [86]. In HIRI, CD40 [48][49][50][51][52][53], OX40 [54], RANKL [55], TRAF2 [87,88], TRAF3 [56][57][58], cIAP1 [89], RELB [59] are upregulated in the liver. CD40, as an M1 macrophage marker gene, is increased in purified Kupffer cells in mice under IR conditions [53].…”
Section: Hepatic Ischemia/reperfusion Injurymentioning
confidence: 99%
“…The defatted liver transplantation can be safely used in liver transplantation in rats, which may lay a solid foundation for its subsequent clinical application. Another experimental animal study by Zhou et al ( 83 ) indicated that HOPE alleviated DCD rat liver I/R by suppressing HECTD3-mediated TRAF3 polyubiquitination, which might be a useful target for improving IRI in DCD liver transplantation. To further investigate the clinical utility of HOPR for DCD liver, Switzerland scholars Dutkowski et al ( 84 ) firstly performed a clinical trial involving eight patients with end stage liver diseases receiving DCD liver transplantation, and found that the application of HOPE for DCD livers appeared to be well-tolerated and easy-to-use, providing better clinical outcomes than the matched liver grafts from cardiac death donors.…”
Section: Contemporary Strategies and Approaches For Hepatic Irimentioning
confidence: 99%